Agricultural Pollution as a Driver for the Ecological Status of Rivers in the Long‐Term Perspective of Nida River Assessment (Central Europe) - A. Cieplok; R. Czerniawski; A. Spyra (Ecology and Evolution, 2025)
ABSTRACT Benthic invertebrates utilized as indicators of river ecological status were examined within the river situated in agricultural catchments as a model system to assess the significance of agricultural pollution in accordance with the European Water Framework Directive (WFD). The extensive study revealed variations in the physicochemical parameters of the water over the years, including pH, NO3, NH4, total dissolved solids, salinity, chlorides, and dissolved oxygen. Notably, the maximum density of invertebrates consistently showed a significant increase during the spring compared to the autumn, while multimetric index values remained comparable. The ecological status fluctuated over the years, with classifications ranging from good and moderate in 2014, moderate in 2017, to good and poor in 2020 and 2023. The significance of the long‐term monitoring study lies in the evolving impact of parameters on the river's ecological status, index component metrics, and MMI values. Additionally, the number of variables exhibiting a significant relationship with individual component metrics has expanded over time. Seasonal variations, as indicated by redundancy analysis results, demonstrated that chlorophyll a and chlorides (in spring) and conductivity (in the autumn) significantly influenced seven metrics and the water quality class. While differences in component metric values were observed in specific years, the water quality class remained comparable over the long term in the two seasons. In the seasons, the MMI_PL value and the quality class were comparable. However, individual component metrics were influenced by various environmental factors, highlighting the importance of considering these factors in interpreting the results of benthic macroinvertebrate studies.